Analysis of the competitive equilibrium based on geographical location - Rodríguez, Vicente; Olarte-Pascual, Cristina; Saco, Manuela (Cuadernos de Estudios Empresariales, 2017)
Geographical location of enterprises has hardly been taken into account in competition models as a decisive variable to reach the competitive equilibrium. In this investigation a spatial analysis has been done in order to optimize the location of a net of sales points under the conditions for Bertrand ´s competition. The main target is to study if the best location of each sales point (strategy of location) matches with the optimal location of the whole net of dealers of a commercial network. To achieve this, location-assignment models have been applied along with p-median algorithms and maximizing the spatial competition, through a Geographical Information System called Flowmap on 25 dealer network located along 1240 postcodes. The results show that the optimal solution for each dealer does not match with the optimal solution for the whole network. This study reveals a new line of research where the results can be widely applied in the business and academic fields.
Keywords: Geomarketing; Geographic Information System (GIS); Automobiles; Location – allocation model; Competitive model.